Destination Country of Field Trip Analysis to Improve Student Cultural Intelligence (CQ) - Ghazali, Achmad; Putranto, Nur Arief Rahmatsyah; Nuraeni, Shimaditya; Prasetyanti, Layung Anindya; Pangestu, Aria Bayu (Jurnal Manajemen Teknologi, 2019)
Abstract. Cultural Intelligence (CQ) is a type of intelligence that can affect someone performance when they work in multi-cultural context. Therefore, university should help their students in increasing their CQ. There are a lot of method that can be used in increasing students’ CQ. One of them is field trip to another country. However, to have optimal effect from this method, chose destination country is an important aspect that must be considered. This research tried to find the suitable destination country by sending students to visit three different countries which were chosen based on the level of national culture similarities based on Hofstede model. The CQ of students was measured before and after the field trips and then the result was compared. The result showed that destination country with similarities in their national culture can give more impact in increasing both students’ CQ and the cognitive aspect of CQ.Keywords: Cultural intelligence, field trip, destination country, hosftede, national culture Abstrak. Kecerdasan kultural (CQ) adalah salah satu jenis kecerdasan yang dapat memengaruhi kinerja seseorang ketika bekerja dalam kontks multibudaya. Karena itu, universitas sebagai lembaga pendidikan tinggi harus membantu siswa dalam meningkatkan CQ. Ada banyak metode yang dapat digunakan untuk meningkatkan CQ siswa, salah satunya adalah karyawisata ke negara lain. Namun, untuk memeroleh hasil optimal dari metode tersebut, pemilihan negara tujuan menjadi komponen yang penting untuk diperhatikan. Penelitian ini mencoba untuk mengidentifikasi negara tujuan seperti apa yang sesuai dengan mengirimkan siswa ke tiga negara yang memiliki tingkat kultur nasional yang berbeda berdasarkan model Hosftede. CQ siswa diukur sebelum keberangkatan dan setelah keberangkan dan dilakukan komparasi terhadap hasil tersebut. Hasil pengukuran menunjukkan bahwa negara tujuan yang memiliki kemiripian kultural nasional yang serupa dapat memberikan dampak optimal pada peningkatan CQ siswa, terutama komponen kognitif.Kata kunci: Kecerdasan kultural, karyawisata, negara tujuan, hosftede, budaya nasional